ANALYSIS OF THE INFLUENCE OF TRANSACTIONAL LEADERSHIP STYLE, COMPENSATION AND WORK MOTIVATION ON WORK PERFORMANCE OF OPERATOR EMPLOYEES OF PT PELABUHAN INDONESIA I (PERSERO) BELAWAN INTERNATIONAL CONTAINER TERMINAL (BICT) BRANCH - Fadhli Ahmad; Ritha F. Dalimunthe; Sitti Raha Agoes Salim (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
Operator Work Performance calculated in the Electronic Performance Management (EPM) Application has decreased from 2013 to 2015. From the results of the pre-survey of the General Manager Leadership Style of PT. Pelindo I BICT Branch, the majority of employees, 78%, showed a transactional leadership style. The discrepancy between attendance according to the Operator and attendance according to the EPM affects the amount of Operator Compensation. This condition is related to Motivation, namely the Motivation of Operators who arrive late and go home earlier than their working hours. The purpose of this study was to determine and analyze the effect of Transactional Leadership Style, Compensation and Motivation on Work Performance. This type of research is quantitative descriptive and the nature of this research is explanatory research. The population in this study was 77 employees and the sample of this study was the entire population to be observed (census research). Data analysis used multiple linear regression. The results of the study showed that partially Transactional Leadership Style had a positive and insignificant effect on Work Performance. However, Compensation and Work Motivation partially had a positive and significant effect on Work Performance. Simultaneously, Transactional Leadership Style, Compensation, and Work Motivation have a significant influence on Work Performance.